Interlanguage Pragmatics Of Criticism Among The Students Of SMA 2 Mejayan - Suharno, Mr.; , Agus Wijayanto, Ph.D; , Dr. Anam Sutopo, M.Hum (2015)
The purpose of this study is exploring the strategy of criticism employed by the students of SMA 2 Mejayan. This study applies descriptive qualitative research. The data in this research were collected by giving discourse completion task (DCT) to 40 students. The DCT comprises nine scenarios of situation which require the students to elicit criticism. The document containing the data of criticism strategy then analyzed based on Nguyen strategy of criticism. The result of the analysis showed some findings. First, the participants tended to employ indirect criticism. Second, the strategy of negative evaluation, request for change, advice about change, and demand for change were dominantly applied over the others in almost status levels. However, some uses of the strategies were inappropriate. This may indicate that the pragmatic competence of the students about the target language is still poor. This poorness could be due to the lack of exposure about the social function of the target language. The various types of criticism strategy applied by the participants indicates that difference status level and social distance may influence their choice of criticism strategies.